Infants Generalize Beliefs Across Individuals - Burnside, Kimberly; Neumann, Cassandra; Poulin-Dubois, Diane (Frontiers in Psychology, 2020)
It has been argued that infants possess a rich, sophisticated theory of mind that is only revealed with tasks based on spontaneous responses. A mature theory of mind implies the understanding that mental states are person-specific. Previous studies on infants’ understanding of motivational mental states such as goals and preferences have revealed that, by 9 months of age, infants do not generalize these motivational mental states across agents. However, it remains to be determined if infants also perceive epistemic states as person-specific. Therefore, the goal of the present study was to use a switch agent paradigm with the classic false belief violation-of-expectation task. Results revealed that 16-month-old infants attributed true and false beliefs to a naïve agent—they did not perceive beliefs as person-specific. These findings indicate that infants’ understanding of beliefs is not as sophisticated as the rich mentalistic view suggests.